SEJARAH-HIDUP Learning Model and the Merdeka Curriculum Reform: A framework for contextual and reflective history learning based on local culture - Mu'arifah Mu'arifah; Tika Mustikawati (Historia, 2026)
The teaching of history in Indonesia remains predominantly centered on national narratives, often disconnected from the lived cultural realities of students. This article introduces the “SEJARAH-HIDUPâ€ model (Students Explore, Record, Aspire), pedagogical framework developed to revitalize history education through contextual, reflective, and community-based learning. Situated within the flexibility of the Kurikulum Merdeka, this model seeks to integrate local cultural heritage as a primary medium for historical inquiry and identity formation. This study employs a qualitative design based on an extensive literature review and triangulation of theories and sources. Findings indicate that the SEJARAH-HIDUP model not only bridges the gap between national curriculum design and students’ sociocultural contexts but also enhances historical consciousness and active citizenship. The model offers both theoretical advancement and practical guidance for integrating local narratives into transformative history education. This work contributes to the growing body of literature advocating for decolonized, place-responsive curricula in postcolonial education systems.